mRNA 3′end processing: a tale of the tail reaches the clinic - Hollerer, Ina; Grund, Kerstin; Hentze, Matthias W.; Kulozik, Andreas (EMBO molecular medicine, 2014)
Abstract Recent advances reveal mRNA 3?end processing as a highly regulated process that fine-tunes posttranscriptional gene expression. This process can affect the site and/or the efficiency of 3?end processing, controlling the quality and the quantity of substrate mRNAs. The regulation of 3?end processing plays a central role in fundamental physiology such as blood coagulation and innate immunity. In addition, errors in mRNA 3?end processing have been associated with a broad spectrum of human diseases, including cancer. We summarize and discuss the paradigmatic shift in the understanding of 3?end processing as a mechanism of posttranscriptional gene regulation that has reached clinical medicine.
Published online 9 October 2013
Gesehen am 27.10.2020